BENDI SEBAGAI ALAT ANGKUTAN DI SOPPENG (STUDI SEJARAH, PROBLEMATIKA, DAN PELESTARIANNYA) TAHUN 2000-2021 - Nurmayanti Nurmayanti; Darman Manda; Mustari Bosra; Andi Ima Kesuma (Universitas Negeri Makassar, 2023)
The aims of this research are (i) to reveal and explain the history of the existence of bendi in Soppeng. (ii) Describe the problems faced by bendi drivers in Soppeng. (iii) Revealing the role of the government and the community in preserving the bendi in Soppeng. In uncovering the existence of bendi in Soppeng Regency, this study uses historical research methods, namely (i) heuristics (ii) criticism (iii) interpretation (iv) historigraphy. In addition, to make it easier to understand the events under study, the authors use theoretical approaches such as (i) functional structure The results of this study indicate that, (i) the history of the existence of bendi in Indonesia which was originally only used for the nobility until finally it could be used in general by the community. (ii) Bendi in Soppeng begins with the existence of a bendi in Soppeng, knowing what it takes to become a bendi driver, types of traditional transportation in Indonesia and how the function and role of a bendi has changed from the colonial period to the modernization era, as well as the author describes the process of gradual decline in the bendi in Soppeng. (iii) regarding the preservation of the bendi carried out by the local government and the community.Tujuan Penelitian ini adalah (i) Mengungkapkan dan menjelaskan sejarah keberadaan bendi di Soppeng. (ii) Menjelaskan problematika yang dihadapi kusir bendi di Soppeng. (iii) Mengungkapkan bagaimana peran pemerintah dan masyarakat dalam pelestarian bendi di Soppeng. Dalam mengungkap keberadaan bendi di Kabupaten Soppeng, penelitian ini mengunakan metode penelitian sejarah yaitu (i)heuristik (ii) kritik (iii) interpretasi (iv) historigrafi.selian itu untuk lebih mudah memahami kejadian yang diteliti maka penulis menggunakan pendekatan teori seperti (i) struktur fungsional Hasil penelitian ini menunjukkan bahwa, (i) sejarah keberadaan bendi di Indonesia yang pada awalnya hanya digunakan untuk para kaum bangsawan saja hingga akhirnya bisa digunakan secara umum oleh masyarakat. (ii) Bendi di Soppeng di mulai dengan keberadaaan bendi di Soppeng, mengetahui apa saja yang dibutuhkan untuk menjadi kusir bendi, jenis-jenis trasportasi tradisional yang ada di Indonesia serta bagaimana perubahan fungsi dan peran bendi dari masa kolonial hingga era modernisasi, serta penulis juga menjalaskan proses kemunduran yang berangsur-asur terjadi pada bendi di Soppeng. (iii) tentang pelestraian bendi yang di lakukan oleh pihak pemerintah daerah serta masyarakat.